2022
DOI: 10.3390/ijms23158103
|View full text |Cite
|
Sign up to set email alerts
|

Halochromic Behavior and Anticancer Effect of New Synthetic Anthocyanidins Complexed with β-Cyclodextrin Derivatives

Abstract: Anthocyanidins, the aglycons of anthocyanins, are known, beyond their function in plants, also as compounds with a wide range of biological and pharmacological activities, including cytostatic effect against various cancer cells. The nature and position of the substituents in the flavylium cation is essential for such biological properties, as well as the equilibrium between the multistate of the different chemical species that are generated by the flavylium cation, including quinoidal base, hemiketal, and cis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In addition, the compounds in studies still showed Topoisomerase I and II inhibitory activity [ 33 ]. Based on the properties of anthocyanidins and aglycones, Păușescu and collaborators (2022) [ 34 ] carried out a synthesis of derivatives of the flavilium cation (7) ( Figure 5 ), these being evaluated for anticancer activities in HCT116 and HepG2 strains. The anticancer effect was influenced by the position (6-, 7-, or 8-) of the methoxy group on the β-ring for the methoxy-4′-hydroxy-3′ methoxyflavilyl cation.…”
Section: Chalcones With Anticancer Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the compounds in studies still showed Topoisomerase I and II inhibitory activity [ 33 ]. Based on the properties of anthocyanidins and aglycones, Păușescu and collaborators (2022) [ 34 ] carried out a synthesis of derivatives of the flavilium cation (7) ( Figure 5 ), these being evaluated for anticancer activities in HCT116 and HepG2 strains. The anticancer effect was influenced by the position (6-, 7-, or 8-) of the methoxy group on the β-ring for the methoxy-4′-hydroxy-3′ methoxyflavilyl cation.…”
Section: Chalcones With Anticancer Activitymentioning
confidence: 99%
“…In addition, the compounds in studies still showed Topoisomerase I and II inhibitory activity [33]. Based on the properties of anthocyanidins and aglycones, Păușescu and collaborators (2022) [34] carried out a synthesis of deriva- In a study carried out in 2019, Hashid and collaborators [32] observed that chalcones that have hydroxy, methoxy, and chlorine groups in the ortho and para positions, have strong inhibitory actions against mechanisms of inflammatory action, such as inhibition of cyclooxygenase. It was also revealed in this study that treatment with these compounds was able to inhibit up to 90% of inflammatory edemas.…”
Section: Colon Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Polyphenols and their synthetic analogs interfere in carcinogenesis by modulating and regulating multiple signaling pathways and transcription factors, membrane-associated receptor tyrosine kinases, fatty acid metabolism and lipid rafts or methylation, together with other emerging targets [ 5 ]. Various synthetic analogues of natural polyphenols demonstrated strong anticancer activity, including (–)-epigallocatechin-3-gallate analogues [ 6 ], synthetic anthocyanidins [ 7 ], or cinnamic acid derivatives [ 8 ]. Some analogues with known anticarcinogenic effect proved even higher stability to metabolic conversion and displayed comparable or higher antitumor activity than the parent compound [ 9 ].…”
Section: Introductionmentioning
confidence: 99%